2023
DOI: 10.1038/s41467-023-41307-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the mechanism of red light-induced melatonin biosynthesis facilitates the engineering of melatonin-enriched tomatoes

Zixin Zhang,
Xin Zhang,
Yuting Chen
et al.

Abstract: Melatonin is a functionally conserved broad-spectrum physiological regulator found in most biological organisms in nature. Enrichment of tomato fruit with melatonin not only enhances its agronomic traits but also provides extra health benefits. In this study, we elucidate the full melatonin biosynthesis pathway in tomato fruit by identifying biosynthesis-related genes that encode caffeic acid O-methyltransferase 2 (SlCOMT2) and N-acetyl-5-hydroxytryptamine-methyltransferases 5/7 (SlASMT5/7). We further reveal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 61 publications
2
2
0
Order By: Relevance
“…The serotonin undergoes acetylation and is converted to N-acetyl-serotonin, which, upon methylation, synthesizes melatonin as a final product. 60 Based on this knowledge, the basic steps involved in melatonin synthesis of EH143 in our analysis seem to be aligned with that observed in plant and animal systems. This is reinforced by our findings of several genes related to tryptophan production and utilization in the whole genome sequence of EH143 (Figure 1D).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The serotonin undergoes acetylation and is converted to N-acetyl-serotonin, which, upon methylation, synthesizes melatonin as a final product. 60 Based on this knowledge, the basic steps involved in melatonin synthesis of EH143 in our analysis seem to be aligned with that observed in plant and animal systems. This is reinforced by our findings of several genes related to tryptophan production and utilization in the whole genome sequence of EH143 (Figure 1D).…”
Section: Discussionsupporting
confidence: 78%
“…In plants, melatonin synthesis begins with the conversion of l ‐tryptophan to tryptamine in the cytoplasm; which is catalyzed by tryptamine‐5‐hydroxylase (T5H); then, tryptamine is converted to serotonin, which is facilitated by acetyl‐coenzyme A (Ac‐CoA). The serotonin undergoes acetylation and is converted to N‐acetyl‐serotonin, which, upon methylation, synthesizes melatonin as a final product 60 . Based on this knowledge, the basic steps involved in melatonin synthesis of EH143 in our analysis seem to be aligned with that observed in plant and animal systems.…”
Section: Discussionsupporting
confidence: 60%
“…Furthermore, numerous studies have shown that a diversely colored light spectrum have broad regulatory effects on metabolism [20,21]. Supplementing red light significantly triggers melatonin accumulation in tomatoes, improves agronomic traits, and provides additional health advantages [22]. Among the factors influenced by light, an appropriate photoperiod can promote the accumulation of metabolites [23].…”
Section: Introductionmentioning
confidence: 99%
“…For example, targeted editing of genes related to drought tolerance in plants has shown promising results in enhancing plantsʼ resilience to drought stress (Li et al 2022). In addition, gene editing technology can be applied to modify the metabolic pathways of medicinal or cash crops to increase the yields of bioactive compounds (Zhang et al 2023).…”
mentioning
confidence: 99%